Comparative analysis of innovative socks made from special synthetic fibers - Giulia Börner; Berat Arici; Carolin Rohrbach; Boris Mahltig (Vestnik of Vitebsk State Technological University)
Functional textiles cover a broad range of different materials and products. The term of functionality is related to properties which are typically not reached with conventional textiles. A functional property can be flame retardancy, antistatic or antimicrobial action. The addition of such functional properties is often demanded for very different types of clothes. To focus this actual report, an overview on functional socks as commercial products is given. A special view is made on the fiber composition of these socks and the thermal insulation of the product. For this, six different commercially available socks are considered which are all claimed to certain functional properties. Also, a reference material – sock without especially claimed functional property – is discussed. All socks contain at least one of the conventional fibers as polyester, polyamide and cotton. Five socks contain elastane in an amount of 2 % to 6 %, to improve the fit of the products. Claimed functional properties are achieved by a content of high-performance fibers in these knitted products. Modacrylic fibers with chlorinated co-unit are used to achieve flame-retardant properties. The use of conductive fibers, as e.g. carbon fibers, leads to antistatic properties. Only for one product a biocide application is mentioned for realization of an anti-insect effect. The socks are investigated by using scanning electron microscopy (SEM) and a test set-up for determining the thermal insulation properties by using a heat camera measuring the surface temperature. The thermal insulation properties of the socks can be clearly determined. However, the intensity of insulation strongly depends on the type of product and the area of measurement – foot ball, instep or heel. Finally, it can be stated that a broad range of different materials are used to create functional socks. For this, socks are excellent examples for textile functional products realized with special synthetic fibers.